Diagnosis of Bladder Cancer by Urine Survivin, an Inhibitor of Apoptosis: A Preliminary Report - Ziaee, Seyed Amirmohsen; Moula, Seyed Javad; Hosseini Moghaddam, Seyed Mohammadmehdi; Eskandar-Shiri, Darioush (Urology Journal, 2009)
Introduction: Survivin is an inhibitor of apoptosis that is expressed in undifferentiated tissues like tumors. Detection of survivin in urine has been proposed as a diagnostic marker for bladder cancer. We evaluated the urine samples of patients with bladder cancer for survivin and compared them with healthy controls. Materials and Methods: The urine specimens of 20 patients with transitional cell carcinoma (TCC) of the bladder (group 1) and 18 controls without cancer (group 2) were collected before cystoscopy and assessed for survivin by reverse transcriptase polymerase chain reaction. Results: All patients except 1 in group 1 were men. Urine specimens were positive for survivin in 18 (90%) and 9 (50%) patients of groups 1 and 2, respectively (P = .007). Sixteen patients with TCC had urine cytology, of which 6 (37.5%) were positive. Urine survivin was positive in all 10 patients with negative cytology. Nine patients in this group had low-grade tumors. Conclusion: Urine survivin seems to have a higher sensitivity than urine cytology, especially in low-grade bladder cancer. The quantitative measurement of survivin in urine by advanced techniques may provide a better diagnostic and prognostic tool. However, the clinical use of survivin and its association with different stages and grades of TCC still requires more studies.